2022
DOI: 10.12688/f1000research.75245.2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Perioperative Cardiovascular Complications in Spine Surgery

Abstract: Background: An increasing number of patients are opting for spine surgery despite the associated risk of cardiovascular complications. The evidence regarding the incidence and risk factors of cardiovascular complications in spine surgery is insufficient. Therefore, we aimed to determine the incidence and risk factors for cardiovascular complications that occur perioperatively in spine surgery. Methods: This retrospective study included all patients who underwent spine surgery between January 2018 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Moreover, the endoscopic transsphenoidal approach had the C/T ratio, Tp, and Ti of 11, 7%, and 0.4, respectively, whereas those for the tumor biopsy had a C/T ratio, Tp, and Ti of 12, 8%, and 0.2, respectively. 3 According to the findings of tumor classification, surgery of meningiomas had effective indexes. The concordance results were similar to what had been shown in the Saringcarinkul and Chuasuwan study, which reported the Tp of patients with meningiomas was 49%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the endoscopic transsphenoidal approach had the C/T ratio, Tp, and Ti of 11, 7%, and 0.4, respectively, whereas those for the tumor biopsy had a C/T ratio, Tp, and Ti of 12, 8%, and 0.2, respectively. 3 According to the findings of tumor classification, surgery of meningiomas had effective indexes. The concordance results were similar to what had been shown in the Saringcarinkul and Chuasuwan study, which reported the Tp of patients with meningiomas was 49%.…”
Section: Discussionmentioning
confidence: 99%
“…However, an overabundance of requests for blood preparation has been observed in prior studies, particularly packed red cells (PRCs). 1 2 3 4 Chotisukarat et al found that the crossmatch to transfusion (C/T) ratio was 4.3% in 1,018 individuals who had elective neurosurgery operations. 3 Additionally, Saringcarinkul and Chuasuwan also studied 377 patients who had undergone neurosurgical operations and reported a high C/T ratio of 6.6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported risk factors for cardiovascular complications following spine surgery, including old age, diabetes, underlying heart disease, and anemia [5,11,24,[31][32][33]. In 2021, Ton et al [34] reported valid factors among modifiable risk factors (MRFs) for postoperative complications in 297,579 patients who underwent lumbar spine fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] De esta manera, al considerar la cirugía de columna lumbar como el procedimiento más frecuente y basarnos en tres grandes estudios sobre complicaciones cardiacas perioperatorias, mismos que contaron con 1,002, 30,339 y 105,505 pacientes, respectivamente, se encontró una incidencia para infarto de miocardio que va de 0.34 a 0.63% dentro de los primeros 30 días del postoperatorio. [21][22][23] En otro estudio, los pacientes que se sometieron a cirugías de fusión vertebral tuvieron una incidencia de IAM de 0.77%, mientras que los pacientes sometidos a procedimientos lumbares sin fusión tuvieron una incidencia de 0.45% (p < 0.001), como consecuencia de que la primera requiere mayor tiempo quirúrgico por su complejidad incrementada y mayor sangrado. 23 Los factores de riesgo para el desarrollo de complicaciones cardiacas observados fueron: una edad mayor a 80 años, diabetes mellitus tipo 2 (DM2), anemia preoperatoria, antecedentes de trastornos cardiacos, sexo masculino y un índice de comorbilidad de Charlson > 3.…”
Section: Epidemiologíaunclassified